Fate of incidental, asymptomatic lesions discovered during percutaneous coronary intervention - (:unkn) unknown (SAGE PUBLICATIONS INC, 2008)
The authors aimed to determine the incidence and angiographic features associated with plaque progression requiring nontarget lesion percutaneous coronary intervention after culprit lesion percutaneous coronary intervention. Of 945 consecutive percutaneous coronary interventions reviewed, 100 patients who required nontarget lesion percutaneous coronary intervention in the following year of the index percutaneous coronary intervention were found and compared with 100 consecutive patients who did not require nontarget lesion percutaneous coronary intervention. Patients with restenosis were excluded. Incidence of clinical plaque progression leading to additional nontarget lesion percutaneous coronary intervention in the year after an index percutaneous coronary intervention was found to be 10.5%. In multivariable logistic regression analyses, the predictors of plaque progression were multivessel disease, unstable angina pectoris, diabetes mellitus, prior percutaneous coronary intervention, and lack of statin use. Initially, lesions that lead to repercutaneous coronary intervention were mostly nonsignificant. Clinical presentation of plaque progression was mostly acute coronary syndrome. Results emphasize the need for further study to refine the methods to identify potentially vulnerable but clinically silent plaques.
Keywords: coronary disease; plaque progression; angioplasty; C-REACTIVE PROTEIN; MULTISLICE COMPUTED-TOMOGRAPHY; RISK-FACTORS; ATHEROSCLEROTIC PLAQUE; VULNERABLE PLAQUE; ARTERY-DISEASE; PROGRESSION; PROFILES; CULPRIT; EVENTS